(3dhGeY GdCSQGQ aj TQM eWGdY GdCfhGQs - (3bWH GdOjf eMehO Hf eSYhO GdTjQGRis; (3GdSQGL GdGQehj , eMehO Hf CHj HcQ Hf CMeO, SQGL GdOjf CHh GdKfGA,J (B682 (3g` s ((3UGdM Hf eMeO Hf YHO GdQMef s)
(3ChdgG (B:s
(3GdMeO ddg ajGV OhGQa GdYhGQa ,hedge MbGFb GdeYGQa , hGgH MjGI GdYGdejf , hQGaY OQLGJ GdYGdejf s
(3BNQgG (B:s
(3hcd ejSQ deG Ndb dg , hGdfbJfY HgPG GdbOQ ef GdcdGe MGeOjf ddg JYGdi Ydi GdZJeGe Je GdcJGH HMeO GdYRjR GdhgGH s
(3GdfSNI ebGHdI Ydi fSNI GdabjI YHO Gddg Hf eMeO GdHMQis
(3HgG HjGV ef GdOGNds
(3HJQbje UaMGJgG HYV GdGVWQGHs
(3cJH GdYfhGfGJ HNW eLhOs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdadSaI hGdefWbs